The Role of Veterinarians in Mass Casualty Disasters: A Continuing Need for Integration to Disaster Management - Holmquist, Lindsey S.; O'Neal, James Patrick; Swienton, Ray E.; Harris, Curtis A. (Frontiers in Public Health, 2021)
The need to prepare veterinarians to serve as part of the disaster medical response for mass casualty incidents has been recognized since at least the 1960's. The potential value of incorporating veterinarians for mass casualty disaster response has been noted by organizations throughout the world. Clinical veterinarians are highly trained medical professionals with access to equipment, medications, and treatment capabilities that can be leveraged in times of crisis. The ongoing threat of disasters with the current widespread healthcare access barriers requires the disaster management community to address the ethical constraints, training deficiencies and legal limitations for veterinary medical response to mass casualty disasters. An ethical imperative exists for veterinarians with translatable clinical skills to provide care to humans in the event of a mass casualty disaster with insufficient alternative traditional medical resources. Though this imperative exists, there is no established training mechanism to prepare veterinarians for the provision of emergency medical care to humans. In addition, the lack of clear guidance regarding what legal protections exist for voluntary responders persists as a barrier to rapid and effective response of veterinarians to mass casualty disasters. Measures need to be undertaken at all levels of government to address and remove the barriers. Failure to do so reduces potentially available medical resources available to an already strained medical system during mass casualty events.